Perspectives of teachers at music schools toward children’s extra-musical abilities promoted by music lessons - Kawase, Satoshi; Kitabayashi, Yuriko (Frontiers in Psychology, 2023)
Musical activities foster children’s social ability. However, the question remains whether professional music teachers consider musical training to have an influence on extra-musical abilities or only on the acquisition of musical skills. We conducted an online survey to collect open-ended responses regarding this question from over 2,000 music teachers in one of the biggest extracurricular fee-charging music school groups in Japan. Teachers’ free descriptions were classified into non-cognitive skills, and frequently occurring words were extracted through text mining. The results showed that, although the primary goal of music teachers who provide fee-charging lessons may be to teach musical skills to their students, they were aware of the effects of music lessons on children’s non-cognitive development. Our study’s main findings include: (1) despite free-descriptions, 92% of teachers reported that children acquired extra-musical abilities, and 98% of these responses were categorized as non-cognitive skills, (2) the most common responses within non-cognitive skills were “collaboration,” “task performance,” and “engaging with others”, and (3) there was a significant positive correlation between teaching experience and frequency of mentioning non-cognitive skills. Views on extra-musical abilities, which experienced music teachers especially had, may improve less-experienced teachers’ perspectives on teaching as well as their social roles and occupational awareness.